Time-resolved X-ray diffraction study of structural changes associated with the photocycle of bacteriorhodopsin. - Koch, M H (1991)
The time course of structural changes accompanying the transition from the M412 intermediate to the BR568 ground state in the photocycle of bacteriorhodopsin (BR) from Halobacterium halobium was studied at room temperature with a time resolution of 15 ms using synchrotron radiation X-ray diffraction. The M412 decay rate was slowed down by employing mutated BR Asp96Asn in purple membranes at two different pH-values. The observed light-induced intensity changes of in-plane X-ray reflections were fully reversible. For the mutated BR at neutral pH the kinetics of the structural alterations (tau 1/2 = 125 ms) were very similar to those of the optical changes characterizing the M412 decay, whereas at pH 9.6 the structural relaxation (tau 1/2 = 3 s) slightly lagged behind the absorbance changes at 410 nm. The overall X-ray intensity change between the M412 intermediate and the ground state was about 9% for the different samples investigated and is associated with electron density changes close to helix G, B and E. Similar changes (tau 1/2 = 1.3-3.6 s), which also confirm earlier neutron scattering results on the BR568 and M412 intermediates trapped at -180 degrees C, were observed with wild type BR retarded by 2 M guanidine hydrochloride (pH 9.4). The results unequivocally prove that the tertiary structure of BR changes during the photocycle.